Spontaneous Closure of a Coronary Artery Bypass Graft Pseudoaneurysm Embedded in a Mediastinal Hematoma - Daniel L. Hess; Gaither W. Horde; Karan Sarode; William S. Morgan; Salmaan Z. Kamal; Jubal R. Watts; Gregory D. Chapman (Case Reports in Cardiology)
Coronary artery bypass graft (CABG) pseudoaneurysms are a rare but often unrecognized clinical entity. They are prone to rupture and hemodynamic compromise and should therefore be on the differential in the appropriate patient. We present a case of a gentleman with a recent CABG surgery who presented with acute onset dyspnea and a large pleural effusion. Imaging revealed a saphenous vein graft pseudoaneurysm embedded in a mediastinal hematoma. Four weeks later, prior to planned stenting, the pseudoaneurysm had spontaneously closed. This case highlights an unusual acute presentation of a CABG pseudoaneurysm and a multidisciplinary approach to its management.